1992
DOI: 10.1016/0736-5748(92)90009-o
|View full text |Cite
|
Sign up to set email alerts
|

Development of the sensory innervation of muscle spindles in the kitten

Abstract: This is a report of the changes observed in the pattern of sensory innervation of muscle spindles in hindlimb muscles of kittens during the first four weeks of life. The structural analysis, made on teased, silver-stained preparations, was complemented by a series of recordings of afferent responses of kitten spindles during ramp-and-hold stretches of the muscle. The primary endings of spindles from newborn animals showed a large degree of variability in their branching pattern and branches formed a network ac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

1994
1994
2009
2009

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 17 publications
0
1
0
Order By: Relevance
“…The bag 1 and earliest chain fibres followed during days 38–41; and both the first recognizable secondary ending and the first tandem‐linked, small capsule ( b 2 c unit) were found during days 41–43. Chain fibres continue to be generated until about the time of birth, and possibly secondary endings also, as Patak et al. (1992) reported that spindles from hind‐limb muscles of new‐born kittens mostly possessed only primary endings, whereas from 1 week post natal the commonest sensory complement was PS.…”
Section: Discussionmentioning
confidence: 99%
“…The bag 1 and earliest chain fibres followed during days 38–41; and both the first recognizable secondary ending and the first tandem‐linked, small capsule ( b 2 c unit) were found during days 41–43. Chain fibres continue to be generated until about the time of birth, and possibly secondary endings also, as Patak et al. (1992) reported that spindles from hind‐limb muscles of new‐born kittens mostly possessed only primary endings, whereas from 1 week post natal the commonest sensory complement was PS.…”
Section: Discussionmentioning
confidence: 99%